2008
DOI: 10.1107/s1600536808013263
|View full text |Cite
|
Sign up to set email alerts
|

Propane-1,2-diammonium bis(6-carboxypyridine-2-carboxylate) dihydrate

Abstract: The reaction of propane-1,2-diamine (pn) and pyridine-2,6-dicarboxylic acid (pydcH2) in a 1:2 molar ratio in aqueous solution resulted in the formation of the title compound, C3H12N2 2+·2C7H4NO4·2H2O or (pnH2)(pydcH)2·2H2O. The structure contains two monoanionic deprotonated forms of pyridine-2,6-dicarboxylic acid molecules (pydcH)−, a diprotonated propane-1,2-diamine (pnH2)2+, and two water mol­ecules. A significant π–π stacking inter­action is observed between the pyridyl rings of the (pydcH)− fragments, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The conformation of N1-C2-C3-N4 chain is extended (torsion angles are 172.0 (4)° and -168.5 (4)° for more and less occupied part, respectively) while the C21-C2 -C3-N4 torsion angles are 50.0 (10)° and -47.0 (11)°. Such conformation -we will call it tg -is the most popular among the simple propane-1,2-diaminium salts (for instance it was found in the structures of hydrogenarsenate (Todd & Harrison, 2005), bis(6-carboxypyridine-2-carboxylate) (Aghabozorg et al, 2008), or tetrafluoro-beryllium (Gerrard & Weller, 2002). The other possibilities are also observed, for instance in some simple hydrates (e.g.…”
Section: Data Collectionmentioning
confidence: 98%
See 1 more Smart Citation
“…The conformation of N1-C2-C3-N4 chain is extended (torsion angles are 172.0 (4)° and -168.5 (4)° for more and less occupied part, respectively) while the C21-C2 -C3-N4 torsion angles are 50.0 (10)° and -47.0 (11)°. Such conformation -we will call it tg -is the most popular among the simple propane-1,2-diaminium salts (for instance it was found in the structures of hydrogenarsenate (Todd & Harrison, 2005), bis(6-carboxypyridine-2-carboxylate) (Aghabozorg et al, 2008), or tetrafluoro-beryllium (Gerrard & Weller, 2002). The other possibilities are also observed, for instance in some simple hydrates (e.g.…”
Section: Data Collectionmentioning
confidence: 98%
“…For general literature on polyamines, see, for example: Hosseinkhani et al (2004); Pospieszna-Markiewicz et al (2006, 2007; Ziebarth & Wang (2009); Itaka et al (2010). For the crystal structures of simple salts of propane-1,2-diaminium, see: Aghabozorg et al (2008); Gerrard & Weller (2002); Lee & Harrison (2003); Todd & Harrison (2005). Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%
“…For background to proton-transfer compounds, see: Aghabozorg et al (2008b). For related structures, see: Aghabozorg et al (2008aAghabozorg et al ( , 2011a; Sharif et al (2010).…”
Section: Related Literaturementioning
confidence: 99%
“…Our research group has previously reported several proton-transfer compounds using pyridine-2,6-dicarboxylic acid (pydcH 2 ), propane-1,2-diamine (p-1,2-da) and propane-1,3-diamine (p-1,3-da), including (p-1,2-daH 2 )(pydcH) 2 .2H 2 O (Aghabozorg et al, 2008d) (Aghabozorg et al, 2008a)…”
Section: S1 Commentmentioning
confidence: 99%